Plasma Gelation as an Overlooked Determinant of Transfection Efficiency in Protein Corona‐Coated Lipid Nanoparticles: Implications for In Vitro–In Vivo Translation - Serena Renzi; Luca Digiacomo; Francesca Giulimondi; Daniela Pozzi; Junbiao Wang; Augusto Amici; Cristina Marchini; Chiara Cassone; Alessandra Zingoni; Fabrizio Marra; Luca Buccini; Francesco Mura; et al. (Advanced Healthcare Materials, 2026)
ABSTRACT A common observation in drug delivery studies is that preincubation of nanoparticles (NPs) with high concentrations of human plasma (HP) markedly reduces in vitro transfection efficiency (TE). This effect is commonly attributed to the formation of a protein corona (PC), which is assumed to impair cellular uptake or intracellular trafficking of gene delivery systems such as lipid nanoparticles (LNPs). However, the evidence presented here suggests an alternative mechanism underlying this phenomenon. To reproduce conditions in which LNPs encounter an excess of circulating proteins, NPs were incubated in HP prior to exposure to cells in standard calcium‐containing culture medium. Under these conditions, plasma undergoes gelation, leading to the formation of a clot‐like network. A combination of complementary approaches, including dynamic light scattering (DLS), fluorescence‐activated cell sorting (FACS), confocal fluorescence microscopy, raster image correlation spectroscopy (RICS), and functional assays evaluating TE and cell viability, demonstrates that this gel‐like matrix restricts LNP diffusion in the extracellular environment. In contrast, coronated LNPs that reach the intracellular space display comparable trafficking behavior, indicating that the PC does not compromise intracellular processing. These findings highlight the importance of extracellular factors when evaluating the impact of the PC and extrapolating in vitro results to in vivo settings.